Recycling of Plastic Polymer: Reinforcement of Building Material Using Polymer Plastics of Used COVID-19 Syringes - Golam Fahim; Md. Tofazzal Hossain; Stapheny Penheiro; Md. Iffat Bin Zakir; Md. Shamsuzzaman; Mohammad Sarwar Morshed; Sakib Hossain Khan; Abu Hamja (Buildings, 2023)
Plastic waste causes severe environmental impacts worldwide and threatens the lives of all creatures. In the medical field, most of the equipment, especially personal protective equipment (PPE), is made from single-use plastic. During COVID-19, the usage of PPE has increased, and is disposed of in landfills after being used once. Worldwide, millions of tons of waste syringes are generated from COVID-19 vaccination. A practical alternative to utilizing this waste is recycling it to reinforce building materials. This research introduces an approach to using COVID-19 syringe plastic waste to reinforce building material as composite concrete. Reinforced fiber polymer (FRP) concrete materials were used to mold cylindrical specimens, which underwent mechanical tests for mechanical properties. This study used four compositions with 0%, 5%, 10%, and 15% of FRP to create cylindrical samples for optimum results. Sequential mechanical tests were carried out on the created samples. These specimens were cured for a long period to obtain water absorption capability. After several investigations, the highest tensile and compressive strengths, approximately 2.0 MPa and 10.5 MPa, were found for the 5% FRP composition samples. From the curing test, the lowest water absorbability of around 5% was found for the 5% FRP composition samples.